Solving Mathematical Model by using Modified Fractional Differential Transform Method with Adomian Polynomials (Journal of Scientific Research, 2024)
In this article, the solution of nonlinear fractional differential equations (FDEs) for disease transmission is discussed in a population believed to maintain a stable size during an epidemic by using a new approach called the fractional differential transform technique (FDTM) along with Adomian polynomials. Also, this method is compared with those that the homotopy perturbation approach produces. Several charts are presented to demonstrate the consistency and simplicity of this method.